Analisis Tingkat Efektifitas Pelaksanaan Pendaftarkan Tanah Melalui Program Pendaftaran Tanah Sistematis Lengkap Di Kantor Badan Pertanahan Nasional Kabupaten Boyolali - Khafida Nur Azizah; Rahayu Subekti (Jurnal Discretie, 2020)
Complete Systematic Land Registration is a land registration activity that is carried out simultaneously for all objects of land registration throughout the territory of the Republic of Indonesia. The author aims to determine the effectiveness of the implementation of land registration through the PTSL program implemented at the Boyolali District BPN Office. The formulation of the problem proposed is: how the implementation of land registration through the PTSL program at the Boyolali District BPN Office, and what supporting and inhibiting factors occurred during the PTSL program implementation. This legal research is empirical research. Data obtained by literature study and research directly from original sources in the form of interviews, which are then processed and analyzed by descriptive methods. The final conclusion of this study is to show that the implementation of land registration through the PTSL program has been running in accordance with the prevailing system structure in Permen N0. 6 of 2018, in the implementation process there are several obstacles and targets that have not been achieved but there is an increase in the achievement of targets every year. From these indicators the authors conclude that the implementation of PTSL has been quite effective.